2008
DOI: 10.1111/j.1469-7580.2008.00962.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional anatomy and muscle moment arms of the thoracic limb of an elite sprinting athlete: the racing greyhound (Canis familiaris)

Abstract: We provide quantitative muscle-tendon architecture and geometry data for the racing greyhound thoracic limb. Muscle mass, belly length, fascicle lengths, pennation angles and moment arms were measured, as were tendon masses and lengths. Maximum isometric force and maximum power were estimated for muscles, and maximum stress and strain were estimated for tendons. Results are compared with other fast quadrupedal runners, and to previously published data in mixed-breed dogs. The implications of the functional ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
97
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(106 citation statements)
references
References 24 publications
7
97
2
Order By: Relevance
“…Longer toes raise the gear ratio (Carrier et al, 1994) by increasing the numerator (lever arm of the GRF), but a smaller plantarflexor moment arm will have the same effect, by decreasing the denominator. Investigations of muscle moment arms in fast-running animals such as the racing greyhound (Williams et al, 2008) revealed that the latissimus dorsi, which has a propulsive role during sprinting, has a high muscle fibre length to moment arm ratio similar to the high fascicle length to moment arm ratios we observed in sprinters. The authors suggested that this high ratio allows generation of large torques over a wide range of motion at fast joint angular velocities.…”
Section: Discussionsupporting
confidence: 60%
“…Longer toes raise the gear ratio (Carrier et al, 1994) by increasing the numerator (lever arm of the GRF), but a smaller plantarflexor moment arm will have the same effect, by decreasing the denominator. Investigations of muscle moment arms in fast-running animals such as the racing greyhound (Williams et al, 2008) revealed that the latissimus dorsi, which has a propulsive role during sprinting, has a high muscle fibre length to moment arm ratio similar to the high fascicle length to moment arm ratios we observed in sprinters. The authors suggested that this high ratio allows generation of large torques over a wide range of motion at fast joint angular velocities.…”
Section: Discussionsupporting
confidence: 60%
“…Friedman et al 1998;Murphy and Mian 1999). Non-stationarity has then been addressed in a variety of ways.…”
Section: Introductionmentioning
confidence: 99%
“…There are several adaptations that can minimise the muscular work required to swing the limb, some of which have been observed in both the cheetah and greyhound. Reduced distal limb mass is observed in both species and will reduce the inertia of the limb (Hudson et al, 2011a;Hudson et al, 2011b;Williams et al, 2008a;Williams et al, 2008b). Muscle insertions that are close to the joint will allow faster joint rotational velocities for a given change in muscle length and are observed in the greyhound, but the cheetah hip and shoulder muscles tend to have long moment arms by comparison (Hudson et al, 2011a;Hudson et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have investigated limb forces during galloping in dogs (Bryant et al, 1987;Walter and Carrier, 2007), but none have examined steady-state galloping in the greyhound, which has a highly specialised morphology compared with other canids (Williams et al, 2008a;Williams et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%